Potential factors influencing the development of thrombocytopenia and consumptive coagulopathy after genetically modified pig liver xenotransplantation. (2012)
Upregulation of tissue factor (TF) expression on activated donor endothelial cells (ECs) triggered by the immune response (IR) has been considered the main initiator of consumptive coagulopathy (CC). In this study, we aimed to identify potential factors in the development of thrombocytopenia and CC after genetically engineered pig liver transplantation in baboons. Baboons received a liver from either an α1,3-galactosyltransferase gene-knockout (GTKO) pig (n = 1) or a GTKO pig transgenic for CD46 (n = 5) with immunosuppressive therapy. TF exposure on recipient platelets and peripheral blood mononuclear cell (PBMCs), activation of donor ECs, platelet and EC microparticles, and the IR were monitored. Profound thrombocytopenia and thrombin formation occurred within minutes of liver reperfusion. Within 2 h, circulating platelets and PBMCs expressed functional TF, with evidence of aggregation in the graft. Porcine ECs were negative for expression of P- and E-selectin, CD106, and TF. The measurable IR was minimal, and the severity and rapidity of thrombocytopenia were not alleviated by prior manipulation of the IR. We suggest that the development of thrombocytopenia/CC may be associated with TF exposure on recipient platelets and PBMCs (but possibly not with activation of donor ECs). Recipient TF appears to initiate thrombocytopenia/CC by a mechanism that may be independent of the IR.